A Novel Combined-Catheter to Monitor Left and Right Atrial Pressures: A Simple and Reliable Method for Pediatric Cardiac Surgery*. Issue 3 (March 2016) - Ding, Jie; Zhang, Quanyi; Li, Lihuan; Zhang, Hao; Yan, Jun; Li, Shoujun; Yan, Fuxia
Abstract : Objective: To introduce a novel combined-catheter to monitor left and right atrial pressures. Design: Prospective observational study. Setting: Fuwai Hospital, China. Patients: A total of 113 pediatric patients (77 men), median age 10.3 months, admitted between July 10, 2014, and February 5, 2015, were divided into two groups: the novel-catheter group and the traditional-method group. Interventions: All patients received routine anesthesia and surgery. Left atrial pressure and central venous pressure (an estimate of right atrial pressure), measured through a catheter needle during surgery, were identified as the "gold standard." A novel combined-catheter, composed of a reformed triple-lumen catheter with a microtube inserted within its central cavity, was used in the novel-catheter group. A traditional triple-lumen catheter to monitor central venous pressure plus another single-lumen catheter to monitor left atrial pressure were used in the traditional-method group. Measurements and Main Results: The novel combined-catheter could accurately monitor left atrial pressure and central venous pressure. Pressure values measured by the novel catheter correlated well with the gold standard (left atrial pressure, R = 0.98; central venous pressure, R = 0.99). Bland-Altman analyses revealed good agreement between pressures measured by the novel catheter and the gold standard. The absolute value of maximum difference was 0.67 mm Hg for left atrial pressure and 0.33 mm Hg for central venous pressure, which are acceptable in clinical practice. Left atrial pressure–monitoring catheter displaced into the right atrium occurred significantly less frequently in the novel-catheter group when compared with the traditional-method group (5 and 12 cases, respectively). Conclusions: This novel combined-catheter was safe and reliable at monitoring left and right atrial pressures, and infusion involved only one catheter without the disadvantages of the traditional method. This new novel method may be particularly useful in pediatric open-heart surgery.